The Role of the Cadherin (CDH) Gene Family in the Carcinogenic Processes of Ovarian Cancer: A Comprehensive Bioinformatics Analysis - Al-Zaalan, Ayoob Radhi; Aziz, Hussam Saadi; Abdulabbas, Noor Fadhil (Asian Pacific Journal of Cancer Biology, 2025)
Background: The persistent challenge of ovarian cancer as a major driver of cancer mortality in the female population stems largely from its tendency toward late-stage identification and frequent disease relapse. The cadherin (CDH) gene family, crucial for cell-cell adhesion, plays complex roles in cancer progression. Objective: Bioinformatics analysis of the CDH gene family in ovarian cancer. Using multiple public databases. Methodology: Transcriptome analysis of cadherin (CDH) gene family in ovarian cancer was performed using Gene Expression Profiling Interactive Analysis 2 (GEPIA2). Prognostic value of differentially expressed CDH genes was assessed using Kaplan-Meier plotter Overall Survival (OS) . Protein-level validation was performed using Human Protein Atlas (HPA) portal which provides immunohistochemistry (IHC). By using GSCALite web server, the assessment of immune cell infiltration was conducted to explore correlations between cadherin expression and tumor immune microenvironment and drug sensitivity analysis was performed to evaluate candidate CDH genes as therapeutic response predictors. Results: Our findings revealed significant differential expression of several CDH genes: CDH1 and CDH4 were downregulated while CDH2, CDH6, CDH11, and CDH23 were upregulated in ovarian cancer tissues. Survival analysis identified CDH6, CDH11, and CDH23 as adverse prognostic markers correlating with poorer overall and progression-free survival, while high CDH2 and CDH4 expression associated with improved survival. Genetic alteration analysis revealed diverse genomic changes across the CDH family, with protein expression data largely corroborating transcriptomic findings. Novel associations between CDH expression and drug sensitivity emerged as potential predictive biomarkers. CDH1 and CDH11 expression correlated with Paclitaxel and Dasatinib resistance, respectively, while CDH2 and CDH6 expression indicated sensitivity to PI3K and Src kinase inhibitors. Conclusion: This study provides comprehensive molecular characterization of CDH family roles in ovarian cancer progression, prognosis, drug response, and immune regulation, establishing specific CDH members as potential diagnostic and therapeutic targets for ovarian cancer.